Here and there : a fire survey - Pyne, Stephen J., 1949- (Pyne, Stephen J., 1949- To the last smoke, 2018)
Fire is special. Even among the ancient elements, fire is different because it alone is a reaction. It synthesizes its surroundings; it takes its character from its context. It varies by place, by culture, and by time. It has no single expression. There is no single way to understand it. In this collection of essays, historian and renowned fire expert Stephen J. Pyne offers his reflections on national and global wildland fire management. Pyne distills the long saga of fire on Earth and its role in underwriting an Anthropocene that might equally be called a Pyrocene. Presented through a mixture of journalism, history, and literary imagination, Here and There moves the discussion of fire beyond the usual formations of science and policy within a national narrative to one of thoughtful interpretation, analysis, and commentary. Centered on the unique complexities of fire management in a global world, Here and There offers a punctuation point to our understanding of wildfire. Included in this volume: How fire policy has changed within the United States; How policy in the United States differs from that in other countries; The history of one of the most famous fire paintings of all time; Suggested next steps for the future of fire research.